Efektivitas Green Sukuk sebagai Instrumen Keuangan Syariah dalam Mitigasi Perubahan Iklim - Ihsan, Moh (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
Green sukuk has emerged as an innovative Islamic financial instrument that aligns Sharia principles with global environmental goals. This study examines the effectiveness of green sukuk in mitigating climate change, with a focus on financing sustainable development projects. Utilizing a qualitative descriptive approach, this paper reviews various green sukuk issuances, particularly those by Indonesia, the first sovereign issuer. The findings reveal that green sukuk not only mobilizes significant funding for renewable energy, energy efficiency, and sustainable transportation but also attracts environmentally conscious investors. Moreover, its compliance with Shariah principles ensures broader acceptance among Muslim-majority markets. The study highlights the dual benefit of green sukuk as both a climate finance tool and a means of expanding the Islamic finance market. However, challenges remain in standardization, project monitoring, and impact measurement. This paper concludes that while green sukuk is still evolving, it presents a promising pathway for integrating ethical finance with climate resilience strategies.